Efecto de la Poda de fructificación por ventanas sobre la brotación, floración y fructificación del Limón Mesina (Citrus Latifolia Tan.) en Finca Artaca S.A., Heredia, Sarapiquí, Costa Rica - Artavia-Mejía, José David (Instituto Tecnológico de Costa Rica, 2019)
The present investigation was carried out in the Artaca SA farm, which is located in Sarapiquí, Heredia, Costa Rica, with the objective of evaluate the effect of the pruning of fruiting in two locations producing of lemon messina (Citrus latifolia Tan.) with different topography, on the production of fresh fruit. Four treatments were evaluated using a Generalized Blocks design (GBD), established in two blocks (Batch 1: Without slope, Batch 2: With slope). The treatments evaluated are classified as T1: fruiting pruning on trees located on land without slope; T2: trees without pruning of fruiting located on land without slope; T3: fruiting pruning on trees located on land without slope; T4: trees without pruning of fruiting located on land without slope. Each block (experimental area) was made up of 20 experimental units, 10 per treatment. The variables evaluated were: number of buds, number of flowers, number of fruits curdled, number of fruits to harvest and diameter of fruit. Two statistical models were used: simplified model (inside the lots) and the complete model (in general). The results showed that within the lot cultivated (simplified model) with slope the pruning of fruiting led to greater formation of flowers, fruit curdled and greater production of fruits to harvest (first evaluation) and that the pruned trees of the lot without slope led to larger diameter fruits compared to fruits from unpruned trees in the lot without slope and trees with and without pruning in the lot with slope. At a general level (complete model) the pruned trees presented greater formation of flowers, of fruit curdled and greater production of harvested fruits than in the trees without pruning (first evaluation). Fruiting pruning generated an induced stress, which stimulates the flowering and subsequent fruiting in cultivated sloping lemon messina trees.
Tesis (Licenciatura en Ingeniería en Agronomía).Instituto Tecnológico de Costa Rica, Escuela de Agronomía, 2019.
Keywords: Producción agrícola; Reguladores de crecimiento; Agricultura; Frutales; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING